A biochemical and physiological study of capture stress in Springbok and forced exercise in sheep - Gericke, Margaretha D.(Margaretha Delina) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1973.